Synoptic CT scan reporting of pancreatic adenocarcinoma to align with international consensus guidelines on surgical resectability: a Victorian pilot. Issue 10 (24th August 2022) - Pilgrim, Charles H. C.; Maciejewska, Anna; Ayres, Nadia; Ellis, Sam; Goodwin, Mark; Zalcberg, John R.; Haydon, Andrew
Abstract: Background: Non‐metastatic pancreatic ductal adenocarcinoma (PDAC) is classified as resectable (R), borderline resectable (BR) or locally advanced (LA). International Consensus Guidelines on these definitions exist, but have not been integrated into everyday Australian practice. The anatomical features on CT imaging lend themselves to synoptic reporting which should enhance completeness, comparability and consistency. Methods: We developed and tested a synoptic report for PDAC derived from the International Consensus Guidelines at two metropolitan pancreatic cancer services to standardize CT reporting in the region. Consecutive scans with suspected PDAC discussed at multidisciplinary meetings were reported using the template between October 2020 and September 2021. A purpose‐built database captured data regarding resectability and image‐quality parameters. Results: Ninety‐five scans were reviewed, 57.9% ( N  = 55) of which conformed to high‐quality pancreatic CT protocols. Of suboptimal scans, meaningful synoptic reports were able to be issued for a further 24/40 (due to metastases in 9, and unequivocal resectability status in 15). Of 79 classifiable scans, 20% were metastatic, 51% deemed resectable, 16% locally advanced and 13% borderline resectable. Discussion: PDAC lends itself to synoptic reporting given the specific anatomical considerations that classify resectability. This relies, however, on high‐quality CT imaging and it was surprising that over 40% of scans reviewed were of suboptimal quality. Despite this, resectability status according to the International Consensus Guidelines was designated for 83% of scans. Optimal treatment algorithms for LA, BR and resectable disease vary widely underscoring the critical importance of accurately differentiating these anatomic subtypes of PDAC, and thus support further implementation of a synoptic report of this nature. Abstract : Synoptic reporting of CT scans for pancreas cancer was tested in a pilot study reported here. The pilot was well received by clinicians and provided valuable data on CT image quality and resectability status designation. Image quality was surprisingly low and rates of borderline resectable disease documented at 13%.